The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1095/biolreprod61.3.764
|View full text |Cite
|
Sign up to set email alerts
|

Subzero Water Permeability Parameters of Mouse Spermatozoa in the Presence of Extracellular Ice and Cryoprotective Agents1

Abstract: Optimization of techniques for cryopreservation of mammalian sperm is limited by a lack of knowledge regarding water permeability characteristics during freezing in the presence of extracellular ice and cryoprotective agents (CPAs). Cryomicroscopy cannot be used to measure dehydration during freezing in mammalian sperm because they are highly nonspherical and their small dimensions are at the limits of light microscopic resolution. Using a new shape-independent differential scanning calorimeter (DSC) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 43 publications
6
70
0
3
Order By: Relevance
“…experimental data can be reconciled (Devireddy et al 1999, Curry 2000. The best-fit parameters obtained in this study with the DSC water transport data (shown in Table 1) during freezing of bovine spermatozoa confirm that this is indeed the case; L pg ¼ 0.02-0.036 mm/min-atm and E Lp ¼ 26.4-42.1 kcal/mol.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…experimental data can be reconciled (Devireddy et al 1999, Curry 2000. The best-fit parameters obtained in this study with the DSC water transport data (shown in Table 1) during freezing of bovine spermatozoa confirm that this is indeed the case; L pg ¼ 0.02-0.036 mm/min-atm and E Lp ¼ 26.4-42.1 kcal/mol.…”
Section: Discussionsupporting
confidence: 72%
“…A dissimilarity between the suprazero and subzero water transport parameters was also found for mouse (Devireddy et al 1999), human (Devireddy et al 2000), horse (Devireddy et al 2002a,b), dog (Thirumala et al 2003) and boar sperm cells. This discrepancy between the membrane permeabilities may be associated with possible changes in the sperm cell plasma membrane during suprazero cooling, including a lipid-phase transition of 0 -4 8C (Noiles et al 1995) and/or cold-shock damage or 'chilling' injury during cooling (Blok et al 1976, Watson 1981, Steponkus 1984.…”
Section: Effect Of Extracellular Ice On Bovine Sperm Membrane Transpomentioning
confidence: 81%
See 3 more Smart Citations